Impact Assessment and Yield Gap Analysis of Composite Fish Culture Technology in North East Region with Special Reference to Arunachal Pradesh, India - Misra, V.K.; Borah, Simanku; Kumar, Neelesh; Kumar, Rajesh; Singh, C.P.; Singh, Shashank; Kumar, Dinesh; Pathak, Mahesh; Tripathi, A.N.; Thungan, Pema Khandu (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The North Eastern States (NES) are the easternmost region of India among them Arunachal Pradesh is a largest hill state and shares its international boundaries with Bhutan in the west, China in the north and Myanmar in the east with a wide range of climates and altitudes. Fish farming is playing a vital role from economic, nutritional and employment point of view in the state, in spite of increase in the production, the current level of fish production is not sufficient to fulfil the requirement, very much far-away to meet out the present consumption demand. Therefore, to identify the yield gap and adoption gap of improved production practice of composite fish culture technology the present study was conducted in the West Kameng district of Arunachal Pradesh. It has been observed that the yields obtained by the farmers are well below those obtained in Govt. Farms and OFT/FLD trials. Carp cultivation practices of 171 farmers were examined on the basis of multistage random sampling. The sample was collected from all the administrative circle of the district West Kameng of Arunachal Pradesh NER India. The average production obtained by the respondents were found only 1.09 t/ha annually, but the range was 2.0 to 2.4-2.8 t/ha in the trials of Govt. farms and OFT/FLDs. The difference of 1.31t/h constituted yield gap under normal practices, these differences were observed due to critical fish farming input availability lacuna on time, the extent to which the farmers adopted the recommended practices, and other socio-economic factors. The study thus clearly showed that the gap is due to the deficiency in adopting the technology along with timely un-availability of quality fish seed and feed which may be bridged only by promotion of the region specific tailored suitable technology of fish farming along with assurance for availability of critical inputs on time.